Problems of Integrating the National and the European Transport - Parvanov, Hristo; Boeva, Olimpia (Research Papers, 2007)
The problems of transport integration in European transport system that may occurs during recent years and how they will be overcomes, is the main task of the present work. On that basis the conditions of Bulgaria different means of transport is investigated in accordance to the tendencies in European transport. Main possibilities for developing the transport relations between Bulgaria and EU member countries are also cleared. The restructuring of national transport, its ecology, and the transport policy as a whole is also subject of investigation. As a conclusion, the most important steps for integrating the national transport in European transport system are determinate.